2018
DOI: 10.1038/s41593-018-0198-x
|View full text |Cite
|
Sign up to set email alerts
|

Parallel circuits from the bed nuclei of stria terminalis to the lateral hypothalamus drive opposing emotional states

Abstract: Lateral hypothalamus (LH) neurons containing the neuropeptide hypocretin (HCRT; orexin) modulate affective components of arousal, but their relevant synaptic inputs remain poorly defined. Here we identified inputs onto LH neurons that originate from neuronal populations in the bed nuclei of stria terminalis (BNST; a heterogeneous region of extended amygdala). We characterized two non-overlapping LH-projecting GABAergic BNST subpopulations that express distinct neuropeptides (corticotropin-releasing factor, CRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
183
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(206 citation statements)
references
References 54 publications
23
183
0
Order By: Relevance
“…We have found with multi-neuron whole cell recordings that the LH does not contain neocortical-like densely connected microcircuits (Figure 1,2). This is in line with the many optogenetically non-connected neurons in this study (Figure 3A,C) and previous studies (Ferrari et al, 2018;Kosse and Burdakov, 2019), as well as the orders of magnitude stronger inputs arising from optogenetically activated long-range sources of input to LH (Giardino et al, 2018;González et al, 2016a). Although we can qualitatively reconcile existing literature on LH intra-connectivity, our findings diverge quantitatively from some published optogenetic datasets: Firstly, we found VGAT-cre à orexin neuron optogenetic connections only in 2/24 cases while Ferrari and colleagues found them in 71/116 cases (Ferrari et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…We have found with multi-neuron whole cell recordings that the LH does not contain neocortical-like densely connected microcircuits (Figure 1,2). This is in line with the many optogenetically non-connected neurons in this study (Figure 3A,C) and previous studies (Ferrari et al, 2018;Kosse and Burdakov, 2019), as well as the orders of magnitude stronger inputs arising from optogenetically activated long-range sources of input to LH (Giardino et al, 2018;González et al, 2016a). Although we can qualitatively reconcile existing literature on LH intra-connectivity, our findings diverge quantitatively from some published optogenetic datasets: Firstly, we found VGAT-cre à orexin neuron optogenetic connections only in 2/24 cases while Ferrari and colleagues found them in 71/116 cases (Ferrari et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…A recent study showed that BNST neurons that project to the LHA can be further subdivided by the expression of the neuropeptidergic genes corticotropinreleasing hormone (Crh BNSTàLHA ) and cholecystokinin (Cck BNSTàLHA ). These neurons show an increase in average calcium activity specific to a rewarding (female mouse urine) or aversive odorant (TMT), respectively (Giardino et al, 2018). Furthermore, chemogenetic activation of Vgat expressing neurons within the BNST increases anxiety-like behavior and leads to activation of the locus coeruleus (LC) (Mazzone et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The BNST is composed of various subnuclei that have unique molecular and functional identities (Giardino et al, 2018;Gungor and Paré, 2016). Therefore, we first assessed the distribution of Pnoc-expressing neurons across the BNST.…”
Section: Expression Of Prepronociceptin Defines a Subpopulation Of Gamentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, recent work supports a broadened role for these neurons in general arousal-related behaviors, including avoidance to aversive stimuli (Viviani et al, 2014). For example, orexin cell activity is strongly increased by negatively valanced emotional stimuli such as predator odor (Giardino et al, 2018). There is also a large literature linking the orexin system with drug motivated behavior, including stress-and cue-evoked drug-seeking as well as the behavioral and physiological syndrome associated with opiate withdrawal (Georgescu et al, 2003).…”
Section: Introductionmentioning
confidence: 98%